Exploring Digital Storytelling as a Pedagogical Tool for Emergent Literacy Skills - Gupta, Noyonika; Sharma, Arushi (THE PRIMARY TEACHER, 2019)
The present study aims to investigate whether a multi-modal intervention using digital storytelling and art can be used to advance emergent literacy skills (specifically Oral Vocabulary and Comprehension), and foster parental engagement in the learning processes amongst children aged 3–6 years. Towards this end, significant positive changes were noted concerning all three objectives. Certain identified features that have possibly contributed to the attainment of objectives include the use of music and jingles in digital stories, frequency of occurrence of certain words in the story, the familiarity of the context of the story, reinforcing words learned through stories by engaging in art activities, child-centric nature of the intervention and adult-child engagement. Despite the positive results, the study suffers from limitations in terms of sample size, composition, and the nature of tools being used. The study has far-reaching implications concerning using digital story-telling and artbased pedagogies in elementary schools for building emergent literacy skills, particularly in low socio-economic contexts.